Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I feel like I'm on the right track, but I don't know if I need to do something else to finish it off...

\begin{align*} f(3x)&=\frac{2}{3-3x}\\ &=\frac{2}{3(1-x)}\\ &=\frac{2}{3}\cdot\frac{1}{1-x}\\ &=\frac{2}{3}\cdot\sum_{n=0}^{\infty}x^{n} \end{align*}

I feel like - OK, so I substituted $x$ with $3x$ so that I could make the fraction look like how I needed it to - but do I need to do something else to reverse the substitution? Or do I have to do this completely differently?

share|improve this question
    
This is correct, now you can substitute $x$ by $x/3$ and you will get the final answer. –  zuggg Jul 6 '13 at 6:49

2 Answers 2

up vote 2 down vote accepted

You method looks great, but you aren't quite finished! The only thing I would change in the beginning is to let $x=3u$ rather than letting $x=3x$. It's a notational thing, but letting $x=3x$ is not a true substitution.

Using my method, at the end you would have $$ f(3u)=\frac{2}{3}\cdot\sum_{n=0}^\infty u^n. $$

To put the function back in terms of $x$, we can make use of our substitution by plugging back in that $3u=x$ and that $u=\frac{x}{3}$ resulting in

$$ f(x)=\frac{2}{3}\cdot\sum_{n=0}^\infty \left(\frac{x}{3}\right)^n. $$

share|improve this answer
    
Ah.. I like that. Just like u-substitution in integration, it is quite easy to see how to back-substitute. Thanks for the insight. –  agent154 Jul 7 '13 at 2:37

\begin{align*} \frac{2}{3-x} &= \frac{2}{3}\frac{1}{1-\frac{x}{3}} \\ &=\frac{2}{3} \sum_{n=0}^\infty \left( \frac{x}{3}\right)^n \end{align*}

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.